PEMBERDAYAAN MASYARAKAT DALAM RANGKA PENANGGULANGAN KEMISKINAN MELALUI PROGRAM PEMBANGUNAN SEMUA KAMPUNG (BANGSAKU) DI KAMPUNG URUMB DISTRIK SEMANGGA KABUPATEN MERAUKE - Yokbeth Gewaljay (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
Community Empowerment in the Context of Poverty Alleviation Through the Development of All Villages (BANGSAKU) in Urumb Village, Semangga District, Merauke Regency. Community welfare in Merauke Regency cannot be realized due to the high level of poverty. Efforts to achieve community welfare must be carried out in a systematic and planned manner so that they receive systematic and continuous treatment. The purpose of this research is to find out community empowerment with efforts to improve the standard of living of the people of Urumb village, Semangga District, Merauke Regency in overcoming poverty. The type of research used is research with a qualitative approach. Research informants totaled 7 (seven) people. The technique used in data collection is using the interviews method(based on interview instructions) observationinterview and documentation. In addition, the data analysis carried out consisted of three stages, namely data summary, data presentation, and drawing conclusions. The results of this study indicate thatcommunity empowerment it didn't go well. Thisis known from several aspects such as the lack of human resources and the lack of awareness from the community in managing natural resources with existing potential. The supporting factor in community empowerment is its abundant natural resources, while the inhibiting factor is the lack of routine training from the government in strengthening community empowerment capacity.